Concept Of Islamic Religious Education In A Multicultural Approach - Alfian, Muhammad; Herningrum, Indah; Putra, Pristian Hadi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study takes a multicultural approach to the concept of Islamic religious education. Differences are unavoidable in a world that is rapidly evolving as it is today. Often, acts of violence, whether in the form of group sarcasm in religious social life or through differences, do not need to occur. Islamic religious education, as part of religious education in schools, is thought to have helped children overcome this from an early age. This study employs library research to develop a theoretical framework and present the data using descriptive qualitative methods. The findings of this study show that multicultural education for students begins at a young age and is critical in developing an understanding of what differences are and how to respond to them. Accordingly, multicultural Islamic religious education aims to develop students with moral values such as love, assistance, forgiveness, tolerance, respect for differences of opinion and religious beliefs, and other attitudes capable of and supportive of human life harmony.